Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/phar.2105
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Open‐label Trial of Early Concomitant Vasopressin and Norepinephrine Therapy versus Initial Norepinephrine Monotherapy in Septic Shock

Abstract: Patients treated with early concomitant vasopressin and norepinephrine achieved and maintained MAP of 65 mm Hg faster than those receiving initial norepinephrine monotherapy, suggesting that overcoming vasopressin deficiency sooner may reduce the time patients spend in the early phase of septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 21 publications
3
54
0
1
Order By: Relevance
“…For example, respondents were less likely to recommend vasopressin as a second‐line vasopressor to raise mean arterial pressure when cost was considered, likely reflecting the preference for a less costly option with epinephrine when the Surviving Sepsis Campaign Guideline recommendation supported either agent . However, it is notable that over two‐thirds of pharmacists still recommended vasopressin even when considering cost and lower levels of evidence, suggesting their practice bias may be influenced by strong personal beliefs regarding physiological bases for vasopressin use but a lack of or controversial supporting data . The scenarios for which there are physiological bases for vasopressin use may represent opportunities for restrictions in the short‐term and research in the intermediate‐to‐long term.…”
Section: Discussionmentioning
confidence: 99%
“…For example, respondents were less likely to recommend vasopressin as a second‐line vasopressor to raise mean arterial pressure when cost was considered, likely reflecting the preference for a less costly option with epinephrine when the Surviving Sepsis Campaign Guideline recommendation supported either agent . However, it is notable that over two‐thirds of pharmacists still recommended vasopressin even when considering cost and lower levels of evidence, suggesting their practice bias may be influenced by strong personal beliefs regarding physiological bases for vasopressin use but a lack of or controversial supporting data . The scenarios for which there are physiological bases for vasopressin use may represent opportunities for restrictions in the short‐term and research in the intermediate‐to‐long term.…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective open‐label study evaluated if early concomitant AVP administration in patients with septic shock reduced the time to reach and maintain a MAP compared with NE alone . Patients receiving early AVP (0.04 units/min) and NE achieved a MAP of 65 mm Hg earlier than patients with NE alone; however, this difference failed to reach statistical significance (5.7 hrs vs 7.6 hrs, respectively; p=0.058).…”
Section: Arginine Vasopressin and Terlipressinmentioning
confidence: 99%
“…Vasopressin also has a “catecholamine‐sparing effect” that results in decreased catecholamine exposure and potentially decreased catecholamine‐related adverse effects . Furthermore, some small studies suggest that early initiation of vasopressin may result in faster resolution of shock and organ failure with decreased vasopressor‐related arrhythmias . The largest prospective randomized controlled trials, however, have been unable to confirm clear clinical benefits to vasopressin.…”
Section: Discussionmentioning
confidence: 99%
“…The Vasopressin vs Norepinephrine Infusion in Patients with Septic Shock (VASST) study was a large, randomized, controlled trial that compared these two therapies in septic shock resistant to low‐dose NE and found no difference in 28‐day mortality (AVP 35% vs NE 39%, P = 0.26) . Other studies, however, have demonstrated faster resolution of shock and decreased organ dysfunction when vasopressin is initiated within 4 to 6 hours of the onset of shock . Further uncertainty exists regarding the optimal order of vasopressor discontinuation …”
Section: Introductionmentioning
confidence: 99%